The Effect of Social Media Marketing on Purchase Decision of K-Pop Idol Iz*One's Albums in Palembang - Siti Ulfa Ridayani; Juhaini Alie; Roswaty Roswaty (International Journal of Marketing & Human Resource Research, 2021)
This study aims to investigate the influence of social media marketing on album purchase decisions, as well as to explore the causes of the wide reach of fans in Palembang City in deciding to purchase the Idol K-pop album IZONE. Data from fans who use Instagram and Twitter are collected through a questionnaire. This study implements a simple linear regression method to analyze data. The results of the investigation show that social media marketing has a significant effect on the decision to buy Idol K-pop album IZONE. This study can provide insights for K-pop idol agencies. The result indicates that to reach Indonesian fans and affect purchasing decision, an agency should optimise their social media marketing strategy.